THE IDEAS OF THE HUMBOLDT MODELAND THE MISSION OF THE UNIVERSITY IN THE CURRENT WORLD - Baberowski, Jörg; Pavlova, Olena (Ukrainian Cultural Studies, 2023)
The interview with Professor Jörg Baberowski is devoted to understanding the mission of the university in the contemporary world.
Keywords: university; Humboldt; current world